The stability of downtown parking and traffic congestion - Richard J. Arnott; Eren Inci (Center for Economic Studies and ifo Institute (CESifo), 2009)
In classical traffic flow theory, there are two velocities associated with a given level of traffic flow. Following Vickrey, economists have termed travel at the higher speed congested travel and at the lower speed hypercongested travel. Since the publication of Walters. classic paper, there has been an on-going debate concerning whether a steady-state hypercongested equilibrium can be stable. For a particular structural model of downtown traffic flow and parking, this paper demonstrates that a steady-state hypercongested equilibrium can be stable. Some other sensible models of traffic congestion conclude that steady-state hypercongested travel cannot be stable, and that queues develop to ration the demand in steady states. Thus, we interpret our result to imply that, when steady-state demand is so high that it cannot be rationed through congested travel, the trip price increase necessary to ration the demand may be generated either through the formation of steady-state queues or through hypercongested travel, and that which mechanism occurs depends on details of the traffic system.
Keywords: R41; L91; 330; Traffic congestion; cruising for parking; on-street parking; hypercongestion; Verkehrsstau; Ruhender Verkehr; Verkehrsaufkommen; Dynamisches Gleichgewicht; Theorie